How to Promote Walking in Women with Fibromyalgia: A Look at Catastrophizing, Goal Conflict, and Avoidance from a Self-Emotional Regulatory Perspective - Carmen Ecija; Lorena Gutiérrez; Patricia Catalá; Cecilia Peñacoba (MDPI AG, 2024)
The aim of this study was twofold: to explore the concordance between two measures of physical activity (accelerometer and IPAQ) among female fibromyalgia (FM) patients, as well as to examine the impact of psychosocial variables (catastrophism, activity avoidance) on walking among these patients. Helplessness, activity avoidance, and commitment to physical activity were evaluated in 132 FM women. After the first assessment, an accelerometer was placed by a psychologist on each participant for seven consecutive days. Eight days later, accelerometers were collected, and participants were evaluated again using the IPAQ. Two models were tested to analyze mediation and a moderated mediation effect. The mediating role of activity avoidance between helplessness and minutes walked was corroborated regarding the objective measure of walking. The effect of helplessness on minutes walked during a week was mediated by activity avoidance and assessed by accelerometers. Cognitive variables played a contextual role when trying to promote exercise. Activity avoidance must be understood as a key variable in physical activity promotion, specifically in the promotion of walking with the aim to do exercise in individuals with FM.